Microscopic characters of the starch granule of the species Phaseolus vulgaris and Phaseolus lunatus (Fabaceae) - Correa Trigoso, Denis E. (2023)
The main objective of the research is to identify the microscopic characters of the starch granuleof the species Phaseolus vulgaris “bean” and Phaseolus lunatus “pallar” (Fabaceae), such as theshape, the hilum, the laminate, the fissure and the extinction cross. Eight seed samples were used,eight varieties of beans, such as caballero, canario, black bean, garbancillo, ñuña type 1, ñuña type 2,ñuña vaquita and panamito; in the same way two pallar, such as large pallar and baby pallar, whichwere acquired in a local market. In each sample, one hundred starch grains were observed, and itwas possible to establish that the starch grains in both species share microscopic characteristics,such as oval, reniform and elliptical shapes; the longitudinal centric fissure with lateral branchesand the extinction cross with curved, straight and wavy arms. However, it was not possible toclearly differentiate at the species level, being linked up to the genus level. Various internal andexternal factors in the plant influence the characters of the starch grain, for this reason it is proposedto expand the sample and record the growth of the plant in order to establish some variations thatcan be diagnosed when analyzing the starch grains of the plant. Each species.